Lecturers' Perceptions of the Use of Technology-Based Legal English Textbooks - Yosi Marita; Yuneva Yuneva; Fitri Anita; Mita Maharani (Institut Agama Islam Negeri (IAIN) Curup, 2026)
The purpose of this study is to explain lecturers’ perceptions of the use of technology-based Legal English textbooks based on numerical data obtained from respondents. A survey approach was employed to gather direct information from respondents regarding their experiences, assessments, and views on the use of technology-based Legal English textbooks. The survey method was considered appropriate as it allowed researchers to reach a number of respondents in a relatively short time and produced data that could be statistically analysed. This approach enabled the researcher to objectively measure the level of lecturers’ perceptions through the collection of data using a structured research instrument. The findings illustrated in the diagram show that the majority of lecturers support the use of technology-based Legal English textbooks, with 74% of respondents stating that they agree or strongly agree. This result has significant implications for legal education, as it demonstrates broad acceptance of digital learning innovations. Such support can serve as a foundation for institutions to formulate official policies that encourage the integration of technology in teaching, while simultaneously strengthening the effectiveness of student learning in developing legal argumentation skills.